2011
DOI: 10.13073/0015-7473-61.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Photoprotection of Wood Coatings by Using Inorganic Nanoparticles as Ultraviolet Absorbers

Abstract: Ultraviolet (UV) light is high-energy radiation that induces degradation of organic compounds, such as wood. To prevent UV damage, several strategies have been used, including creating a UV light barrier at the wood surface. The most common strategy is to apply a coating to the wood surface. However, coating alone may not be effective enough to protect wood exposed outdoors. For example, clear coatings often contain additives to protect the material from UV radiation (hindered amine light stabilizers, quencher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 0 publications
2
36
1
Order By: Relevance
“…Similarly, Cristea and Riedl showed that zinc oxide and titanium dioxide nanoparticles improved the durability of clear coatings on black spruce wood exposed to accelerated weathering [66]. Auclair and co-workers compared the ability of different inorganic (zinc or copper oxide nanoparticles) and organic photostabilizers (UVA/HALS) to prevent the discolouration of clear-coated sugar maple panels exposed to accelerated weathering [67]. The best photoprotection was obtained with zinc oxide nanoparticles (2% w/w) [67].…”
Section: Inorganic Photostabilizersmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Cristea and Riedl showed that zinc oxide and titanium dioxide nanoparticles improved the durability of clear coatings on black spruce wood exposed to accelerated weathering [66]. Auclair and co-workers compared the ability of different inorganic (zinc or copper oxide nanoparticles) and organic photostabilizers (UVA/HALS) to prevent the discolouration of clear-coated sugar maple panels exposed to accelerated weathering [67]. The best photoprotection was obtained with zinc oxide nanoparticles (2% w/w) [67].…”
Section: Inorganic Photostabilizersmentioning
confidence: 99%
“…Auclair and co-workers compared the ability of different inorganic (zinc or copper oxide nanoparticles) and organic photostabilizers (UVA/HALS) to prevent the discolouration of clear-coated sugar maple panels exposed to accelerated weathering [67]. The best photoprotection was obtained with zinc oxide nanoparticles (2% w/w) [67]. The combination of inorganic and organic UV absorbers was also effective and showed synergistic effects on the gloss of the coatings [67].…”
Section: Inorganic Photostabilizersmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies report wood surface coatings based on inorganic nanoparticles acting as UV absorbers (Rao et al 2016). Generally, these nanoparticles are semiconductor materials which absorb UV light via electron transition between conduction band and valence band but are transparent to visible light (Aloui et al 2007;Auclair et al 2011;Fu et al 2015). For instance, southern pine specimens were vacuum impregnated by nano-ZnO dispersions for UV protection (Clausen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The main drawback of such treatments is the leaching of added particles over time, lowering the protection efficiency, and necessitating regular application of new layers. Facing this challenge, a mixture of inorganic UV absorbers in a transparent organic coating to obtain highly durable and efficient UV protection coatings was reported recently (Auclair et al 2011). ZnO-based acrylate coatings were applied to impregnate wood to reduce yellowing under UV exposure (Weichelt et al 2010).…”
Section: Introductionmentioning
confidence: 99%